Understanding sensory dysfunction : learning, development and sensory dysfunction in autism spectrum disorders, ADHD, learning disabilities and bipolar disorder - Emmons, Polly Godwin, 1960- (Jessica Kingsley Publishers, 2005)
Understanding Sensory Dysfunction is a clear and comprehensive resource to identifying and addressing sensory dysfunction in children, using a range of practical strategies to help them reach their full potential at home, at school and in the community. The authors explain the causes, contributing factors, symptoms and associated behaviors of sensory dysfunction, particularly when found in conditions such as autism spectrum disorders (ASDs), ADHD and bipolar disorder. Focusing on early intervention, they provide a host of tried and tested integration activities, assessment and curricular modif.